BENEFITING THE EXPERIENCE OF INTERNATIONAL STUDENTS: PRINCIPLES AND POLICIES OF INTERNATIONALISATION OFUNIVERSITI MALAYSIA SABAH - Irma Wani Othman; Muhammad Safuan Yusoff; Abu Bakar Abdul Hamid; Herlina Jupiter; Hasbullah Awang, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The Strategic Plan of Universiti Malaysia Sabah (UMS) 2013-2017 is outlined to highlight seven (7) Universityâ€™s Key Fields that include the UMS-KRAs (UMS Key Result Areas), MMS-KRA3 based on a strategic objective, â€œEnhancing International Visibility and Reputationâ€ (UMS, 2013). To achieve the motive, UMS emphasised on the needs to increase the quality of higher education in contributing to the development of the countryâ€™s education. In regard to the proposed goal, the increment of enrolment of international students is deemed necessary to make UMS relevant and competitive. Issues that are brought forward in this paperwork refer to the empirical data of 20 chosen informants from 10 faculties in Universiti Malaysia Sabah. A handful of the respondents were interviewed individually and thoroughly, while the rest were involved in a group discussion. This research focuses on two objectives which are (i) to identify the experience of first year international students in UMS and (ii) to propose the principles and policies of internationalisation of UMS based on the experience of international students. The results obtained have contributed to (i) the understanding of oneâ€™s self-reflection individual expatriation experience to the international students who wish to further their studies overseas and (ii) the significant input to the universityâ€™s management team by contributing the empirical data and useful perspectives as regards the intake issues of international students to be implemented specifically into the principles and policies of internationalisation of UMS